A 2-year follow-up study on muscle size and dynamic strength in teenage tennis players - Kanehisa, H.; Kuno, S.; Katsuta, S.; Fukunaga, T. (Scandinavian Journal of Medicine & Science in Sports, 2006)
Growth trends in the cross-sectional area of the quadriceps femoris (CSAQF) and its dynamic strength in 12 teenage tennis players (six boys and six girls), aged from 10.7 to 13.2 years at the onset of the study, were investigated through a 2-year follow-up survey. CSAQF values at the three levels (proximal, mid, and distal to the knee joint) and dynamic torques during knee extensions at three pre-set velocities (1.05, 3.14, and 5.24 rad/s) were determined year by year, i.e., three times (T1, T2, and T3), using magnetic resonance imaging and an isokinetic dynamometer, respectively. In both genders, the CSAQF values at the three levels tended to increase across the measurement times, with greater gains in the boys than in the girls at the levels mid and distal to the knee joint. Among these changes, only the CSAQF at the level proximal to the knee joint significantly increased regardless of changes in both skeletal age and body height. The ratios of torque to the sum of CSAQF at the three levels (T/CSA) at 3.14 and 5.24 rad/s for the boys and at 5.24 rad/s for the girls were significantly higher in T2 and T3 than T1. Further, the relative increases in torque and T/CSA values at 3.14 and 5.24 rad/s were greater in the boys than the girls. The findings presented here indicate that young tennis players who are in the earlier stage of adolescence increase the CSA of the QF muscle beyond normally expected growth change at the level proximal to the knee joint and show a predominant development in torque generation capability during high-velocity knee extensions, with a greater gain in boys compared with girls.